Analysis of Information Technology Governance Priorities at PTKIN Using The COBIT 2019 Framework - Hidayah, Nur Aeni; Junaidi, Junaidi; Fetrina, Elvi; Ratnawati, Suci (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
Risk management is a part of information technology (IT) governance, enabling organizations to safeguard their information assets effectively and efficiently. It involves identifying potential risks, planning mitigation strategies, and establishing relevant policies. An interview with the Head of Pustipanda at Syarif Hidayatullah State Islamic University (SIU) Jakarta revealed that the university underwent an IT governance audit by the National Cyber and Crypto Agency in 2020, with results indicating the need for significant improvements. Given the critical role of the Academic Information System (AIS) as a strategic IT asset in higher education, effective management is essential. This study aims to evaluate the IT governance maturity of Pustipanda using the COBIT 2019 framework and to identify key governance domains that should be prioritized for improvement. The study focuses on the IT governance of Pustipanda Syarif Hidayatullah SIU Jakarta, selected as a sample from the broader population of PTKIN (State Islamic Religious Colleges) in Indonesia. Using the COBIT 2019 framework, the research identifies 22 IT governance domains prioritized for implementation, with six domains categorized as top priority. These findings provide actionable insights for IT governance enhancement, particularly in academic institutions. The methodology presented can serve as a reference for other PTKIN to assess and prioritize IT governance domains according to their specific organizational needs, supporting the development of more secure, efficient, and well-governed IT environments in higher education institutions.